Operationalizing professionalism: A meaningful and practical integration for resident education. (5th August 2013) - Nichols, Brent G.; Nichols, Laura M.; Poetker, David M.; Stadler, Michael E.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Review contemporary definitions of professionalism and apply them to resident evaluation and education. Data Sources Review of PubMed, Medline, and Google Scholar. Review Methods Review of articles and bibliographies from 1980 to 2012 for professionalism definitions, evaluation, and education in resident training was performed. Results Our initial search returned 291 articles. Sixty‐seven articles were included in the final review. Definitions of professionalism often focused on attitudes and traits such as honesty, altruism, self‐reflection, reliability, and respect for others. The operationalization of such abstract definitions is challenging as they are subject to variable interpretations when translated into measurable behaviors. Despite the challenges, specific behavioral benchmarks can be developed and utilized for evaluation with available methods including patient/nurse surveys, faculty observation, objective structured clinical exams (OSCE), ethical reasoning tests, and completion of administrative tasks. Curriculums have often been lecture‐based, limiting the ability to transmit professional values and behaviors. Professionalism is taught most effectively through multiple modalities including mentorship, faculty role modeling, self‐reflection, and resident professionalism portfolios. For professionalism evaluation and education to be effective, the curriculum should be developed as a collaborative effort between residents and faculty. Conclusions Professionalism training requires practical, behavior‐based definitions of professional conduct. Once professional expectations are defined, multiple methods should be used to comprehensively evaluate the learner. Professionalism curriculums must be interactive and promote development through a variety of methods with the goal to improve resident performance in this critical core competency. Laryngoscope, 124:110–115, 2014